Pengembangan Pengolahan Turunan Salak Pada KWT Agro Abian Salak Di Desa Sibetan, Karangasem - Puspita, Ni Putu Lianda Ayu; Miranti, Putu Gita Suari; Yani, Ni Wayan Merry Nirmala (Universitas Pahlawan Tuanku Tambusai, 2024)
Sibetan Tourism Village in Karangasem Regency, famous as the center of salak plantation, has limited salak fruit processing infrastructure, causing farmers difficulties in sustainable processing. Dependence on the harvest season and the perishable characteristics of salak fruit emphasize the need for good post-harvest handling. The results of discussions with KWT (Kelompok Wanita Tani) Agro Abian Salak showed that the processed salak dates are still not optimal due to simple equipment, inconsistent processing, and manual bookkeeping. Through this assistance, it is expected that KWT can develop skills in processing salak derivative products so that they can compete in local and territorial markets. The methods used include training, technical assistance, and marketing assistance. The results of this activity include increased knowledge of KWT members in processing salak derivative products, product diversification, improved product quality, and increased market access. In conclusion, this service activity makes a positive contribution to local economic development through increasing the added value of salak derivative products and empowering KWT in improving their welfare.